Mental toughness in Judo: perceptions of coaches - Silva, Virgílio; Dias, Cláudia; Corte-Real, Nuno; Fonseca, António Manuel (Revista de Artes Marciales Asiáticas, 2018)
The aim of this research was to explore coaches’ perceptions about mental toughness characteristics in competitive Judo, in light of current single-sport mental toughness literature. Nine Portuguese Judo coaches from different levels of achievement (non-elite, sub-elite and elite) were interviewed. The protocol used for semi-structured interviews was based on Personal Construct Psychology “sociality” and “dichotomy” corollaries (Kelly, 1991). A total of 162 verbatim transcribed pages resulted as raw data. Properties and dimensions of the conceptual categories emerged from the data. Inductive content analysis revealed 22 attributes of mental toughness. Only eight were mentioned by all participants: resilience, self-motivation, self-confidence, self-improvement, work discipline, attention regulation, emotional regulation and competitiveness. In reference to previous researches exploring mental toughness on a single sport, our results in Judo reinforced large similarities across sports. However, slight differences were discussed in relation to three mental toughness characteristics not previously identified in literature: combativity, self-esteem and adaptability. In addition, other attributes were found to be peculiar to Judo, but not exclusive, due to its form of expression: tactical awareness, combativity and self-presentation regulation. Combativity was the only attribute that stood out as being rather peculiar to Judo.